2001
DOI: 10.1104/pp.010542
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Plastid Division Proteins in the Chloroplast Stromal Compartment Establishes a New Functional Relationship between FtsZ1 and FtsZ2 in Higher Plants

Abstract: Chloroplast division is driven by a macromolecular complex containing components that are positioned on the cytosolic surface of the outer envelope, the stromal surface of the inner envelope, and in the intermembrane space. The only constituents of the division apparatus identified thus far are the tubulin-like proteins FtsZ1 and FtsZ2, which colocalize to rings at the plastid division site. However, the precise positioning of these rings relative to the envelope membranes and to each other has not been previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
120
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 50 publications
11
120
0
Order By: Relevance
“…Three independent T2 lines were analyzed for both AtFtsZ1-1 and AtFtsZ2-1. We observed more or less severe inhibition of plastid division in the transgenic plants, consistent with previous results (Osteryoung et al, 1998;McAndrews et al, 2001). Figure 6 shows control cells (mesophyll, Figure 6A; bundle sheath, Figure 6B) and cells displaying little or no plastid division defects ( Figures 6C, 6G, and 6H) (;55% of the observed plants, Table 2), intermediate phenotypes (15% of the plants), or very severe phenotypes ( Figures 6D, 6E, 6F, 6I, and 6J) (22% of the plants).…”
Section: Overexpression Of Atsula Inhibits Plastid Divisionsupporting
confidence: 92%
See 4 more Smart Citations
“…Three independent T2 lines were analyzed for both AtFtsZ1-1 and AtFtsZ2-1. We observed more or less severe inhibition of plastid division in the transgenic plants, consistent with previous results (Osteryoung et al, 1998;McAndrews et al, 2001). Figure 6 shows control cells (mesophyll, Figure 6A; bundle sheath, Figure 6B) and cells displaying little or no plastid division defects ( Figures 6C, 6G, and 6H) (;55% of the observed plants, Table 2), intermediate phenotypes (15% of the plants), or very severe phenotypes ( Figures 6D, 6E, 6F, 6I, and 6J) (22% of the plants).…”
Section: Overexpression Of Atsula Inhibits Plastid Divisionsupporting
confidence: 92%
“…It has previously been reported that overexpression of either AtFtsZ1-1 or AtFtsZ2-1 results in a dominant negative effect causing severe plastid division defects McAndrews et al, 2001). In these experiments, plastid division was more or less severely affected in the different lines.…”
Section: Overexpression Of Atsula Inhibits Plastid Divisionmentioning
confidence: 77%
See 3 more Smart Citations